1977
DOI: 10.1002/1097-0142(197709)40:3<1318::aid-cncr2820400349>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to survival following resection for gastric carcinoma.Analysis of 903 cases

Abstract: This report is based on 903 patients with resections for gastric carcinoma between October 1957, and July 1969, entered in controlled trials of adjuvant therapy with Thio-TEPA and FUDR. Neither Thio-TEPA nor FUDR, as administered , prolonged survival. The extent of disease at the time of curative surgery is related to survival for the first 36 months postoperatively. Involvement of lymph nodes, resection of the esophagus, and serosal penetration are predictive of recurrence up to 36 months. There appear to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…As shown in previous studies based on univariate and multivariate analyses, T-stage, lymph-node involvement and vascular invasion are the most important histological parameters predicting the prognosis of gastric cancer patients (Serlin et al, 1977;Okada et al, 1983;Curtis et al, 1985;Miwa, 1984;Maruyama, 1987;Bozzetti et al, 1990;Gabbert et al, 1991). When these parameters were compared with the prognostic value of TCD, T-stage, followed by vascular invasion and lymph-node involvement were the histological parameters of highest prognostic value in our study, too.…”
Section: Discussionsupporting
confidence: 77%
“…As shown in previous studies based on univariate and multivariate analyses, T-stage, lymph-node involvement and vascular invasion are the most important histological parameters predicting the prognosis of gastric cancer patients (Serlin et al, 1977;Okada et al, 1983;Curtis et al, 1985;Miwa, 1984;Maruyama, 1987;Bozzetti et al, 1990;Gabbert et al, 1991). When these parameters were compared with the prognostic value of TCD, T-stage, followed by vascular invasion and lymph-node involvement were the histological parameters of highest prognostic value in our study, too.…”
Section: Discussionsupporting
confidence: 77%
“…Also of those that had TNM staging, 57.9% were stage II. These findings seen to suggest poor outcome, and thus support studies that found that, the deeper the penetration of the gastric wall by tumour the greater the chance of metastases and hence the poorer the prognosis [26][27][28].…”
Section: Colorectal Cancerssupporting
confidence: 81%
“…Although adjuvant therapy after radical ~astric resection has been expected to be the most promising treatment for stomach cancer, there is no long-term follow-up report to demonstrate improvement of survival with use of adjuvant therapy and many pessimistic results [34,35] have been reported !nstead. Several regimens for adjuvant chemotherapy have been suggested and evaluated clinically.…”
Section: Resultsmentioning
confidence: 99%